Design of next-generation therapeutic IgG4 with improved manufacturability and bioanalytical characteristics. Issue 1 (1st January 2020) - Chen, Zhiqiang; Qian, Yueming; Song, Yuanli; Xu, Xuankuo; Tao, Li; Mussa, Nesredin; Ghose, Sanchayita; Li, Zheng Jian
ABSTRACT: Manufacturability of immunoglobulin G4 (IgG4) antibodies from the Chemistry, Manufacture, and Controls (CMC) perspective has received little attention during early drug discovery. Despite the success of protein engineering in improving antibody biophysical properties, a clear gap still exists between rational design of IgG4 candidates and their manufacturing suitability. Here, we illustrate that undesirable two-peak elution profiles in cation-exchange chromatography are attributed to the S228P mutation (in IgG4 core-hinge region) intentionally designed to prevent Fab-arm exchange. A new scaffolding platform for engineering IgG4 antibodies amenable to bioprocessing and bioanalysis is proposed by introducing an "IgG1-like" single-point mutation in the hinge or CH1 region of IgG4S228P. This work offers insight into the design, discovery, and development of innovative therapeutic antibodies that are well suited for robust biomanufacturing and quality control.